In the Land of Free People: A Turkish Liberal Utopia between the State and the Individual (American Journal of Islam and Society, 2000)
Presented here is an analysis of the political thought of Ahmet Agaoglu,one of the sounding boards of Mwtafa Kemal Atatiirk. In his utopianwork “In the Land of Free People,’’ he is preoccupied with the idea ofmaking Turkey a “progressive” state so that it can attain the standardachieved by Western civilization. How it is done does not matter, aslong as the country is put on the path of “liberalism,” which to him isthe shortcut to development. The liberalism suggested by Agaogu isnot via privileging individual rights through popular will (as in theWest), but through manipulation by the state; even if it must beachieved through despotic practices.